Synthesis of stilbenoids via heck reaction in ionic liquid accelerated by microwave irradiation / Noor Azimah Abdullah - Abdullah, Noor Azimah (2008)
Ionic liquids, being composed entirely of ions have interesting characteristics that make them suitable to be used as solvents for Heck reaction. This study was carried out to investigate the effects of ionic liquids and microwave irradiation on Heck reaction. 4- iodoanisole and 4-iodophenylbenzyl ether were used as the aryl halide, and 4- methoxystyrene as the alkene. Six different reaction conditions were used in order to synthesize stilbenes via palladium-catalyzed Heck reactions. The coupling of 4- iodoanisole and 4-methoxystyrene were done for six hours in ionic liquids bmimPF and bmimlsf'a. The yields obtained were 43.69% and 24.27% respectively. The coupling between 4-iodophenylbenzyl ether and 4-methoxystyrene gave the yield of 49.02%. Heck reaction between 4-iodoanisole and 4-methoxystyrene in ionic liquid bmimBF4, accelerated by microwave irradiation produced as much as 67.96% stilbene in less than two hours. The results showed that the reaction time could be shortened to just several hours to produce the stilbene as compared to the reaction in conventional solvents such as DMF that normally takes between one to three days.